If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x(2x-3)(x+7)=0
We multiply parentheses ..
3x(+2x^2+14x-3x-21)=0
We multiply parentheses
6x^3+42x^2-9x^2-63x=0
We do not support expression: x^3
| 180+x=120 | | 5x+24=51+2xx= | | 4(-4+6)=9(-4-4x) | | 3=-k/2-5 | | 3x2−17x=−10 | | (4x+12)+2°=180 | | (10x+3)-153=180 | | 2m/15=1/3 | | 9x+4=3x+16=180 | | 4^x=8.2^x | | X=280.22y | | 2s–6=–4 | | 2(s–6)=–4 | | 3x^2−17x=−10 | | 43+n=95 | | -2(-5b-2)=-4(-2b+3) | | 2x(x+4)=70 | | 7x-4=5x+10=180 | | -3.65+7.4x-6.04=21.76 | | s=180(17-2) | | 8x+100=80 | | -6n+4(5n-3)=-110 | | 7x^2+12x+27=0 | | 5(2x-4)=16-2x | | 32=-5w+3(w+8) | | -13.2(x+9.6)=-356.4 | | X=y+280 | | -7(8x+5)=7(-3x-8) | | 10x-20+5x+5x+5=180 | | 4a+3–a=24* | | n+18=11 | | 5f+7-2=2(f+2)+2f-1 |